1989
DOI: 10.1093/ajh/2.8.631
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Left Ventricular Mass and Noninvasive Monitoring of Blood Pressure

Abstract: We studied the relationship between left ventricular mass index (LVMI) and blood pressure (BP) monitored during 24 hours in 35 normotensive and 58 hypertensive patients with no treatment for more than three months. We found a close correlation between LVMI and the average daytime systolic BP (r = 0.68). Other parameters derived from BP monitoring were also correlated with LVMI: daytime diastolic BP (0.54), nighttime systolic and diastolic BP (0.61 and 0.54), pulse pressure (0.58), the average of the five highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…27 Several studies did not find any correlation between target organ damage and BP variability assessed with intra-arterial 3 and patient-activated 2 or fully automatic 4,28,29 noninvasive monitoring. However, the small sample size 3,4,28,29 or the low number of ambulatory BP readings 2 do not allow for drawing definitive conclusions from these studies. Interestingly, Schmieder et al 30 found that BP at work and during sleep, but not its rise elicited by mental or physical stress, was a determinant of LV hypertrophy.…”
Section: Discussionmentioning
confidence: 96%
“…27 Several studies did not find any correlation between target organ damage and BP variability assessed with intra-arterial 3 and patient-activated 2 or fully automatic 4,28,29 noninvasive monitoring. However, the small sample size 3,4,28,29 or the low number of ambulatory BP readings 2 do not allow for drawing definitive conclusions from these studies. Interestingly, Schmieder et al 30 found that BP at work and during sleep, but not its rise elicited by mental or physical stress, was a determinant of LV hypertrophy.…”
Section: Discussionmentioning
confidence: 96%
“…However, there are other studies where the cited association was not found [10][11][12] or was lost in the presence of other well-known risk factors [13,14]. An explanation for these apparently contradictory results may be the selection of the index [standard deviation (SD)] used for quantifying variability [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise quantification of short‐term BPV requires beat‐to‐beat BP recording, its assessment is also possible, even if less accurately, through the use of intermittent noninvasive 24‐hour ambulatory BP monitoring (ABPM). However, studies in which short‐term BPV was estimated by ABPM yielded conflicting results …”
mentioning
confidence: 99%